2014
DOI: 10.1007/s00113-013-2532-9
|View full text |Cite
|
Sign up to set email alerts
|

Mason-I-Fraktur – eine harmlose Verletzung?

Abstract: In light of the complications, Mason I fractures must be reevaluated. They remain the domain of conservative treatment but close follow-up is recommended to recognize possible complications early in order to prevent stiffness, chronic instabilities, and osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 18 publications
0
5
0
6
Order By: Relevance
“…Wir führten eine systematische Suche der Onlinedatenbanken PubMed, EMBASE, CINAHL und The Cochrane Library durch. Als Suchtermini benutzten wir "(radial head) AND ( [2]. Diese Studie fasst die gängige Datenlage systematisch zusammen und zeigt, dass Begleitverletzungen mit hoher Regelmäßigkeit vorkommen, auch bei den "einfachen" Mason-I-Frakturen.…”
Section: Materials Und Methodenunclassified
See 3 more Smart Citations
“…Wir führten eine systematische Suche der Onlinedatenbanken PubMed, EMBASE, CINAHL und The Cochrane Library durch. Als Suchtermini benutzten wir "(radial head) AND ( [2]. Diese Studie fasst die gängige Datenlage systematisch zusammen und zeigt, dass Begleitverletzungen mit hoher Regelmäßigkeit vorkommen, auch bei den "einfachen" Mason-I-Frakturen.…”
Section: Materials Und Methodenunclassified
“…Die zitierten Studien zeigten aber allesamt ein signifikant schlechteres Ergebnis bei Begleitverletzungen [22]. Michels [2]. Für den klinischen Alltag ergeben sich für uns aus dieser Studie mehrere Fakten.…”
Section: Materials Und Methodenunclassified
See 2 more Smart Citations
“…These cases demonstrated that even undisplaced radial head fractures may be caused by a dislocation mechanism. 30 Therefore, the authors recommend reexamination and, potentially, an early MRI for patients with complicated courses following Mason I fractures.…”
Section: Mason Imentioning
confidence: 98%